1998
DOI: 10.1088/0031-9155/43/2/014
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the influence of the partial volume effect on SPECT activity quantitation with 3D modelling of spatial resolution in iterative reconstruction

Abstract: Quantitative parameters such as the maximum and total counts in a volume are influenced by the partial volume effect. The magnitude of this effect varies with the non-stationary and anisotropic spatial resolution in SPECT slices. The objective of this investigation was to determine whether iterative reconstruction which includes modelling of the three-dimensional (3D) spatial resolution of SPECT imaging can reduce the impact of the partial volume effect on the quantitation of activity compared with filtered ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 34 publications
0
24
0
3
Order By: Relevance
“…The Ordered Subsets Expectation Maximization (OSEM) reconstruction algorithm [1] with a 3D model of the point-source response function (psrf) has been investigated for these purposes. Pan et al [2] and Pretorius et al [3] found resolution and quantification improvements with the algorithm for Tc-99 m. With I-131, 3D OSEM better recovered the activity in small targets, compared to an algorithm with a 1D model. This fact was shown employing six subsets and 100 iterations to reconstruct projections from a seven-sphere phantom acquired by a Marconi Prism camera [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Ordered Subsets Expectation Maximization (OSEM) reconstruction algorithm [1] with a 3D model of the point-source response function (psrf) has been investigated for these purposes. Pan et al [2] and Pretorius et al [3] found resolution and quantification improvements with the algorithm for Tc-99 m. With I-131, 3D OSEM better recovered the activity in small targets, compared to an algorithm with a 1D model. This fact was shown employing six subsets and 100 iterations to reconstruct projections from a seven-sphere phantom acquired by a Marconi Prism camera [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, iterative reconstruction methods such as those derived from the Maximum-Likelihood Expectation-Maximization scheme 33 can incorporate all kind of information such as scatter or spatial variation of the system's PSF to compensate for nonstationary resolution (see Chapter 4). Those methods have been explored both in SPECT 14,[34][35][36] and PET. 37 Some other iterative reconstruction methods not only incorporate some model of the scanner's PSF, but can also incorporate a priori anatomical information from e.g., MRI, in an attempt to compensate for partial volume effect, both in SPECT 38 and PET.…”
Section: Reconstruction-based Correction Methodsmentioning
confidence: 99%
“…Die Auswirkungen der CDR-Kompensation auf die rekonstruierten Bilddaten wurden eingehend qualitativ [30], quantitativ [13,18,19] und aus klinischer Sicht [7,11,17] untersucht. Es konnte gezeigt werden, dass CDR-korrigierte Bilder nicht nur eine verbesserte Auflösung und einen höheren Signal-zuRausch-Abstand aufwiesen sondern auch eine geringere Variabilität des Rauschens zeigten (• " Abb.…”
Section: Auswirkungen Der Cdr-kompensation Auf Rekonstruierte Bilddatenunclassified
“…Ausgehend von den Unterschieden im iterativen Rekonstruktionsprozess mit und ohne CDR wird klar, dass eine anwendungsspezifische Optimierung der Aufnahme-und Verarbeitungsparameter für einen erfolgreichen Einsatz von korrektiven Rekonstruktionsmethoden essenziell ist [7,10,11,20]. Es konnte in einer Vielzahl von klinischen Anwendungen eindeutig gezeigt werden, dass die CDR-Kompensation einen verbesserten Kontrast von Läsionen liefert [18,31]. Auf der Grundlage von mathematischen Berechnungen und auch als Ergebnis von Befundungsstudien konnte außerdem bewiesen werden, dass sich die Nachweisbarkeit sowohl für heiße als auch für kalte Läsionen durch die Anwendung der CDR-Kompensation erhöht [11,31].…”
Section: Auswirkungen Der Cdr-kompensation Auf Rekonstruierte Bilddatenunclassified
See 1 more Smart Citation